Changes in recreational behaviors of outdoor enthusiasts during the COVID-19 pandemic: analysis across urban and rural communities. Issue 1 (14th August 2020) - Rice, William L; Mateer, Timothy J; Reigner, Nathan; Newman, Peter; Lawhon, Ben; Taff, B Derrick
Abstract: The COVID-19 pandemic presents not only a global health crisis but has also disrupted the daily lives of people around the world. From a leisure perspective, urban outdoor enthusiasts are one group particularly impacted by the pandemic and the subsequent institutional response. Stay-at-home orders and physical distancing recommendations serve as potential inhibitors to outdoor recreation activities central to the lifestyles and wellbeing of outdoor enthusiasts. In urban areas, where these orders and recommendations are most restrictive, the potential impacts on recreation behavior are most consequential. This study provides an empirical analysis of the COVID-19 pandemic's impact on the recreational behaviors of outdoor enthusiasts across urban and rural communities. Results suggest that the frequency of outdoor recreation participation, distance travelled to participate in outdoor recreation and distance travelled beyond roads during outdoor recreation have declined significantly more among outdoor enthusiasts residing in urban areas than urban clusters or rural areas.